2022
DOI: 10.1108/jcm-08-2020-4024
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural consequences of verbally expressed and unexpressed customer rage emotions

Abstract: Purpose The purpose of this study is to distinguish those emotions which customers express verbally during a failed remote service encounter from those which they do not. The study further attempts to investigate the post-consumption customer behaviour of verbally expressed and unexpressed negative customer emotions. Design/methodology/approach The authors used a survey-based research design. The hypotheses were tested through the “partial least squared structural equation modelling” method. Findings This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Verbal retaliatory emotions like anger cause the customer to spread NWOM (Awasthi & Kumar, 2022;McColl-Kennedy et al, 2009). Further, Furrer et al (2021) examined how captive emotions ranging from anger to joy induce NWOM as a customer coping strategy by venting.…”
Section: Affective Drivers Of Nwom/newommentioning
confidence: 99%
See 2 more Smart Citations
“…Verbal retaliatory emotions like anger cause the customer to spread NWOM (Awasthi & Kumar, 2022;McColl-Kennedy et al, 2009). Further, Furrer et al (2021) examined how captive emotions ranging from anger to joy induce NWOM as a customer coping strategy by venting.…”
Section: Affective Drivers Of Nwom/newommentioning
confidence: 99%
“…The pleasure arousal theory (Mehrabian & Russell, 1974) bifurcates rage emotion as retaliatory and rancorous rage emotions when a failure occurs. Verbal retaliatory emotions like anger cause the customer to spread NWOM (Awasthi & Kumar, 2022; McColl‐Kennedy et al, 2009). Further, Furrer et al (2021) examined how captive emotions ranging from anger to joy induce NWOM as a customer coping strategy by venting.…”
Section: Dimensions Of Nwom and Newommentioning
confidence: 99%
See 1 more Smart Citation
“…Langner et al (2014) highlighted that judgments shape emotional responses and feelings toward a brand. While brand emotions have been studied (Awasthi and Kumar, 2022) as well as consumer opinions based on perceived information developed during information gathering or from past consumption experience (Kim et al, 2014), the CBBE literature lacks insight into the connection between consumer brand judgment and feeling (Keller, 2016). Wine brand literature suggested that consumers use their subjective expertise on ROO and quality to form opinions about preferred wines (Ferreira et al, 2022).…”
Section: Validationmentioning
confidence: 99%
“…Prior studies highlighted creating emotional connections between brands and consumers. Emotion, as per this study, is a set of behavioral tendencies including expressions, actions and other behaviors that are associated with brand purchase and consumption (Awasthi and Kumar, 2022). Positive feelings strengthen consumer-brand bonds, driving actions like repurchasing and recommending (Cheung et al.…”
Section: Consumer-based Brand Equity Model (Cbbe)mentioning
confidence: 99%